2003
DOI: 10.1354/vp.40-2-216
|View full text |Cite
|
Sign up to set email alerts
|

Brodifacoum Toxicosis in Two Neonatal Puppies

Abstract: Abstract. Eight out of a litter of 13 puppies were either born dead or died within 48 hours of birth. Three puppies that died shortly after birth were necropsied. Two puppies had hemorrhage in the thoracic and peritoneal cavities, intestinal serosa, and meninges. The third puppy was smaller than the other two puppies but did not have detectable hemorrhage. Brodifacoum, a second-generation coumarin anticoagulant, was detected in livers from the two puppies with hemorrhage. The dam did not have clinical signs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…Internal bleeding also causes generalized pain; fever; II. AGENTS THAT CAN BE USED AS WEAPONS OF MASS DESTRUCTION lameness from bleeding into a joint; bleeding into the thorax or abdomen, brain, or pericardium; or sudden death (Braithwaite, 1982;Berny et al, 1995;Munday and Thompson, 2003).…”
Section: Animal Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…Internal bleeding also causes generalized pain; fever; II. AGENTS THAT CAN BE USED AS WEAPONS OF MASS DESTRUCTION lameness from bleeding into a joint; bleeding into the thorax or abdomen, brain, or pericardium; or sudden death (Braithwaite, 1982;Berny et al, 1995;Munday and Thompson, 2003).…”
Section: Animal Toxicologymentioning
confidence: 99%
“…The most common type of exposure is direct poisoning by eating a cereal-based bait containing the rodenticide. The most commonly affected household pets are dogs, followed by cats, hamsters, rabbits, and pet birds Park and Leck, 1982;Boermans et al, 1991;Woody et al, 1992;Hornfeldt and Phearman, 1996;Peterson and Streeter 1996;McConnico et al, 1997;Robben et al, 1997Robben et al, , 1998Munday and Thompson, 2003;Radi and Thompson, 2004) (Table 18.4).…”
Section: Household Pets and Farm Animal Exposuresmentioning
confidence: 99%
“…Contaminants that impact reproduction are found among nearly all types of chemicals used in urban areas, including anticoagulant rodenticides, insecticides, heavy metals, and industrial effluents. Primary effects of contaminants may include reduced female fertility and increased chance of miscarriage, reduction in sperm counts, altered gonad development, and hormonal or endocrine disruption (Vos et al 2000;Munday and Thompson 2003;Choi et al 2004;Robinson et al 2005). Laboratory experiments showed that lead exposure affected seminal vesicles and epididymes in cotton rats ( Sigmodon hispidus; McMurry et al 1995).…”
Section: Reproductive Impairmentmentioning
confidence: 99%
“…Hormonal disturbances in wildlife caused by endocrine disruptors include sex changes in riverine fish and marine snails, reproductive failure in birds, and abnormalities in the reproductive organs of American alligators ( Alligator mississippiensis; reviewed in Vos et al 2000). Anticoagulant rodenticides, the most commonly used rodenticides worldwide, are associated with increased chance of miscarriage, in utero toxicity, and decreased sperm counts (Munday and Thompson 2003;Robinson et al 2005). The breeding success for two bird species, blue tit ( Cyanistes caeruleus) and great tit ( Parus major), was reduced as a result of exposure to heavy metal pollution from a copper smelter (Eeva et al 2003(Eeva et al , 2009.With the varied and sometimes intensive use of contaminants in urban landscapes, reproductive impacts may be much more common than we know.…”
Section: Reproductive Impairmentmentioning
confidence: 99%
“…Non-target species are potentially at risk from direct consumption of bait and also through eating poisoned rodents (Berny et al, 1997). Recently, ten cases of rodenticide poisoning in dogs were observed in Texas Vet Medical Diagnostic Laboratory and two neonatal puppies (Munday and Thompson, 2003). Eason and Spurr (1995) reported brodifacoum rodenticide toxicity in 200, one week old chicks, in which hundred percent mortality was observed.…”
Section: Introductionmentioning
confidence: 99%